2020
DOI: 10.31294/jeco.v4i2.8223
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Social Media dan Brand Image Terhadap Purchase Decision Melalui Buying Interest

Abstract: The purpose of this research is to determine the most influential and important variables that cause the low totally of the peoples has been visited at Parangtritis beach Yogyakarta in accordance with the problems that have been formulated. A sample size of 97 that can represent the population is determined using the Krejcie-Morgan method. The method of analysis in this study is to use a variance-based analysis of Structural Equation Modeling (SEM), namely Partial Least Square (PLS). The sampling technique in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
0
0
4
Order By: Relevance
“…Where the influence of brand awareness (X2) on purchasing decisions (Y2) has a path coefficients value of 0.221 which is close to +1 value, a T-Statistic value of 3.650 (> 1.96), and a p-value of 0.000 (<0.05), so it can be concluded that the fifth hypothesis (H5) is accepted and brand awareness (X2) has a positive and significant effect on purchasing decisions (Y2), from these results, it can be concluded that if brand awareness (X2) increases by one unit, then the purchase decision (Y2) increases by 0.214. The results in this study are supported by findings from previous research where Sutiyati et al (2020) and Ansari et al (2019) found that brand awareness has a significant effect on purchasing decisions.…”
Section: Hypothesis Test Resultssupporting
confidence: 90%
“…Where the influence of brand awareness (X2) on purchasing decisions (Y2) has a path coefficients value of 0.221 which is close to +1 value, a T-Statistic value of 3.650 (> 1.96), and a p-value of 0.000 (<0.05), so it can be concluded that the fifth hypothesis (H5) is accepted and brand awareness (X2) has a positive and significant effect on purchasing decisions (Y2), from these results, it can be concluded that if brand awareness (X2) increases by one unit, then the purchase decision (Y2) increases by 0.214. The results in this study are supported by findings from previous research where Sutiyati et al (2020) and Ansari et al (2019) found that brand awareness has a significant effect on purchasing decisions.…”
Section: Hypothesis Test Resultssupporting
confidence: 90%
“…Variabel brand image berpengaruh positif dan signifikan terhadap purchase decision (Sutiyati et al, 2020). Citra merek berpengaruh secara signifikan terhadap keputusan pembelian (Lestari et al, 2019) Manajemen, Vol.…”
Section: Worldwide Smartphone Shipments and Annual Growth Canalys Sma...unclassified
“…F-hitung 39,040 disertai sigifikansinya 0,000 menjabarkan bahwasanya model layak dipergunakan Pengolahan data mendapatkan hipotesis pertama diterima yakni terdapat pengaruh positif dan signifikan antara citra merek ke keputusan pembelian smartphone pada konsumen iPhone di Kota Denpasar dimana tingkat signifikansinya 0,001< 0,05. Variabel brand image berpengaruh positif dan signifikan terhadap purchase decision (Sutiyati et al, 2020). Citra merek berpengaruh secara signifikan terhadap keputusan pembelian (Lestari et al, 2019).…”
Section: Tabel 11 Deskripsi Jawaban Responden Terhadap Promosiunclassified
“…Alasannya Produk MS Glow dibuat oleh perusahaan yang mempunyai reputasi yang baik sehingga merasa lebih aman menggunakan produk kosmetik MS Glow. Hasil ini mendukung penelitian yang dilakukan oleh (Latif and Hasbi 2021;Sutiyati, Welsa, and Lukitaningsih 2020)…”
Section: Pembahasanunclassified